2018
DOI: 10.21699/jns.v7i1.677
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mortality in an Australian Tertiary Surgical Neonatal Intensive Care Unit

Abstract: Aim: The aim of the study was to estimate mortality rate and trend in the neonate admitted to a surgical neonatal intensive care unit.Methods: This study was a retrospective cohort analysis of all neonatal (from birth to <44 weeks corrected post-menstrual age) deaths that occurred in a single institution between 2000 and 2015. Mortality rate and trend over 16 years was evaluated. Mortality rates for neonates with surgical and cardiac diseases were analysed with the trend over a fifteen year period reported.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…A systematic review in African countries found that the neonatal surgical mortality rate reduced from 36.9% in previous decade to 29.1% in the subsequent decade [10]. On the contrary, neonatal mortality in a report from Australia was 3.6% over 16 years [11]. In Japan, mortality linearly declined from 12% in 1993 to 6.6% in 2013 [12].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review in African countries found that the neonatal surgical mortality rate reduced from 36.9% in previous decade to 29.1% in the subsequent decade [10]. On the contrary, neonatal mortality in a report from Australia was 3.6% over 16 years [11]. In Japan, mortality linearly declined from 12% in 1993 to 6.6% in 2013 [12].…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal general surgical mortality has significantly improved globally in the last three decades. [1][2][3] Ad-vancements in neonatal intensive care, anesthesia, nursing, and medical technology have transformed the outcomes in all babies, including preterm babies.…”
Section: Discussionmentioning
confidence: 99%